Peran Etika, Moral, dan Akhlak dalam Konteks Pendidikan dan Kehidupan Masyarakat Kampus - Sugianto Sugianto; Maya Syafira Br Bangun; Anindya Hanifah; Nanda Fitrianingsih (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2025)
Rapid social change and massive technological developments have influenced the values ​​entrenched in campus communities, including ethics, morals, and ethics. This article aims to deeply analyze these concepts and their relevance in the context of education and modern society. The research used a literature review method from five accredited national scientific journals. The results of the study indicate that ethics, morals, and ethics have fundamental differences in terms of their sources and applications, yet they complement each other in shaping students' personalities. In the digital era, shifting values ​​demand a new approach to character education to instill these values ​​adaptively. It is clear that strengthening ethics, morals, and ethics through education not only shapes individuals with character but also serves as a foundation for building a civilized campus community. This article discusses ethics, morals, and ethics from an Islamic perspective and how they are applied in everyday life. This article aims to explain the differences and relationships between these three concepts, as well as the importance of ethics in shaping a Muslim's personality. Ethics is a collection of principles, values, or morals that guide a person's behavior. Ethics also relates to good and bad things in behavior, which include a person's moral rights and obligations in living in society.